(untitled) (Economic studies journal, 2019)
of Heads of Scientific Departments’ Opinions at Sirte University This study dealt with two subjects, organizational justice and job alienation, on the basis of their being of organizational phenomena that focus on human resource and it affect in performance of this important resource of the organization andthrough it in the organizational performance. The study aims to detect the effect of organizational Justice in job alienation; it based on one main hypothesis, this hypothesis states thatthere is a significant effect of organizational Justice in job alienation. University of Sirt was selected to be the field of the study and testing its hypothesis, and the heads of the scientific departments were selected to be the study society. The number of respondents was (63) of the total heads of scientific departments. By using a number of statistical tools the hypotheses were tested. The most important results of the study is the heads of scientific departments of Sirt University have a moderate levels of the organizational justice , as well as they have a moderate levels of job alienation, the study also showed the effect oforganizational justice was significant injob alienation across distributive justice and procedural justice in varying degrees. The study presented a set of recommendations in respect of how to enhance the levels of organizational justice of heads of scientific departments